The Heat Treatment Effect on Microstructure for Arc Welding of Dissimilar Steel to copper (University of Thi-Qar Journal for Engineering Sciences, 2014)
The purpose of this paper is to be familiarize with the microscopic structure of the welding specimen, before and after heat treatment in which the pure copper ( OFHC ) has been welded to the low carbon steel ( ASTMA36 ) by the method of fusion welding ( Arc Welding ) using covered welding electrode (SMAW) .A 12mm thick plates of the two metals were used.The plate have been prepared (Single Butt Joint ) where the dissimilar plates copper to steel were welded using ( Ecusu8 ) electrodes . The heat treatment has been carried out to the specimen at 600Co,700Co then cooled down in the oven . The microscopic test for the welded specimen has been carried out before and after the heat treatment .Before heat treatment It was clear that there exist a separating limit from the steel side with zigzag indicating that interaction was happened giving a ( Non-epitaxial ) structure with opening windows accompanied by diffusion of masses from the base metal inside the added metal ,while after heat treatment, it is found that more zigzag and opening cracks in the steel side filled with the added metal by the process of ( Brazing ) and excess clearness of diffusion process with diffused metal taking a tree shapes , While from the copper side, it showed ( Epitaxial Growth ) No existence to any cracks was noticed , but there was a granulated growth especially when heated up to 700Co     .